Comparison of theoretical and experimental values of tensile properties of injection moulded polylactic acid – kenaf fibre biocomposite - Anuar, Hazleen; Ahmad, Zuraida; Kovacs, J. G.; Tabi, T. (2011)
This paper focuses on the fabrication of polylactic acid (PLA)–kenaf fibre (KF) biocomposite using intermeshing co-rotating twin screw extruder and then injection moulded for tensile properties characterization. The effect of kenaf fibre loading from 0-20 wt% was studied. The average of kenaf fibre aspect ratio is 30. Tensile strength and modulus show similar trend where significant improvement was attained at 20 wt% kenaf fibre content. Scanning electron micrograph of tensile fracture specimen has revealed the hypothesis of interaction between fibre and matrix subsequently amplified the tensile properties. It is an interesting finding where the experimental value of tensile modulus was 15% higher than theoretical tensile modulus at 20 wt% KF. Additionally PLA-KF bicomposite produced have high specific strength and specific modulus. This could suggest that kenaf fibre may be incorporated into PLA to reduce mass of the end product and substantially reduced the cost of raw materials.